Socio-medical studies of individuals self-treating with helminths provide insight into clinical trial design for assessing helminth therapy - Venkatakrishnan, Aarushi; Sarafian, Joshua T; Jirků-Pomajbíková, Kateřina; Parker, William (Parasitology international, 2022)
The virtually complete loss of intestinal worms, known as helminths, from Western society has resulted in elimination of a range of helminth-induced morbidities. Unfortunately, that loss has also led to inflammation-associated deficiencies in immune function, ultimately contributing to widespread pandemics of allergies, autoimmunity, and neuropsychiatric disorders. Several socio-medical studies have examined the effects of intentional reworming, or self-treatment with helminths, on a variety of inflammation-related disorders. In this study, the latest results from ongoing socio-medical studies are described. The results point toward two important factors that appear to be overlooked in some if not most clinical trials. Specifically, (a) the method of preparation of the helminth can have a profound effect on its therapeutic efficacy, and (b) variation between individuals in the effective therapeutic dosage apparently covers a 10-fold range, regardless of the helminth used. These results highlight current limits in our understanding of the biology of both hosts and helminths, and suggest that information from self-treatment may be critical for clinical evaluation of the benefits and limits of helminth therapy.
Keywords: Humans; samoléčba; Self-treatment; Inflammation; lidé; zvířata; Helminth; zánět; cizopasní červi; Helminths; Self Medication; helmintoterapie; Clinical trials; klinické zkoušky jako téma; výzkumný projekt; Dose escalation; Clinical Trials as Topic; Animals; Research Design; Therapy with Helminths